Geographic Variation in Body Size and Weight of Willow Ptarmigan - West, George C.; Weeden, Robert B.; Irving, Laurence; Peyton, Leonard J. (ARCTIC, 1970)
Reports results of multiple range test comparisons of wing, tail and net body weight measurements of 2600 specimens collected in Alaska and adjacent Yukon Territory. Populations from different geographic areas showed statistically significant differences but uniformity within recognizable subspecies. Lagopus lagopus alascensis has the largest range in Alaska and occurs at least to Old Crow in the Yukon. L.l.albus occurs from central Yukon Territory eastward and south to northern British Columbia and west into Alaska in the upper Tanana valley and south of the Alaska Range to the Susitna River. L.l. alexandrae occupies the Alaska and Kenai Peninsulas and a narrow margin of the Gulf of Alaska coast south into British Columbia. L.l. murei is distributed on Kodiak Island, the Shumagins and the Aleutians from Unimak westward. The present distribution of these subspecies may be explained in part by their distribution at the time of the Wisconsin glaciation and their subsequent dispersal. Variations géographiques de la taille et du poids du Lagopède des saules. De multiples comparaisons de mesures des ailes, de la queue et du poids net de 2,600 spécimens de lagopède des saules (Lagopus lagopus) recueillis en Alaska et dans la partie adjacente du territoire du Yukon, ont démontré des différences statistiquement significatives entre les populations des différentes aires géographiques, mains ont aussi indiqué une surprenante uniformité parmi les populations désignées comme sous-espèces reconnaissables.Les précédentes distributions d'habitat, basées sur la couleur du plumage et la taille du bec, distinguaient L. l. alascensis de L. l. albus à la frontière Alaska-Yukon. Sur la base des nouvelles mesures, on croit que la population du L. l. alascensis plus gros s'étend vers l'Est dans le territoire du Yukon au moins jusqu'à Old Crow, tandis que le L. l. albus plus petit s'étend vers l'Ouest à travers l'Alaska, dans la haute vallée de la Tanana et au Sud de la chaîne alaskienne jusqu'à la Sustina. On suppose que la ...